2002
DOI: 10.1080/014608602753504856
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parents' Participation in the Care of Their Child Undergoing Day Surgery: Pilot-Study

Abstract: In Canada, more than 100,000 children have procedures in day surgery units. In spite of certain programs designed to prepare those children and their parents for the procedures and events that take place in a hospital, the parents' role during the day stay is not openly and directly approached. Although many pediatric centers recognize the importance of the role of the family in the life of children with health problems, the perceptions of parents with children undergoing day surgery and their role in the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
1
17
2
1
Order By: Relevance
“…Professionals recognized the importance of parents in the process of involvement, but perceived parents as lacking in necessary skills. This is in contradiction with previous research findings in which parents felt that they were able to participate in their child's care if they were given information and guidance from the staff (Chapados, Pineault, & Tourigny, 2002;Tourigny, Chapados, & Pineault, 2005). Lack of time is a barrier mentioned at all three sites, has been mentioned in previous literature (McKiel, 2002), and is a finding congruent with heavy workloads and the shortage of health professionals in both countries.…”
Section: Discussioncontrasting
confidence: 79%
“…Professionals recognized the importance of parents in the process of involvement, but perceived parents as lacking in necessary skills. This is in contradiction with previous research findings in which parents felt that they were able to participate in their child's care if they were given information and guidance from the staff (Chapados, Pineault, & Tourigny, 2002;Tourigny, Chapados, & Pineault, 2005). Lack of time is a barrier mentioned at all three sites, has been mentioned in previous literature (McKiel, 2002), and is a finding congruent with heavy workloads and the shortage of health professionals in both countries.…”
Section: Discussioncontrasting
confidence: 79%
“…No significant difference was also observed between the ranking of infants and number of infants in terms of the levels of mothers' performance in the care of premature infants [24]. The results of this study were inconsistent with the study by Chapados et al The results of this study showed that parents with higher education levels, and younger parents, are more inclined to participate, while aged parents are more inclined to leave the care to the staff [25]. Perhaps the reason for this difference in the results is induced by difference in demographic characteristics of studied groups which have unique characteristics and also different sample numbers.…”
Section: Discussioncontrasting
confidence: 57%
“…Parents have expressed their need for more information and support from nursing staff regarding pain management 6,15 . Parents need clear explanations of the surgical procedure and subsequent medical treatment their child will receive, what part they might play in this, and time to validate their understanding 10 . If parents received clear guidelines about postoperative care, they could assume a greater part in the care of their child and manage their child's pain better 17 .…”
Section: Introductionmentioning
confidence: 99%